Based Learning Training Lesson Study to Improve the Quality of Elementary School Teachers Kartasura Muhammadiyah, Indonesia - Tjipto Subadi; Sabar Narimo; Erlina Farida Hidayati (Warta LPM, 2022)
Aim of study is to examine and describe 1) the effectiveness of lesson study as a model of Muhammadiyah Elementary School teacher training to improve the quality of learning 2) validation of lesson study as a model of Muhammadiyah elementary school teacher training to improve the quality of learning. This research used an approach of descriptive-qualitative phenomenology and the research design used the modified class action-based lesson study. The subject of study included the Primary School teachers Muhammadiyah of Kartasura, and the informants were the teachers, headmasters, supervisor. The data gathering employed questionnaires, interview, and observation The data analysis used the first order understanding and second order understanding with an interactive model, including data reduction, data display, and conclusion/verification. The conclusion of this research is, 1) The effectiveness of lesson study as a model of coaching Muhammadiyah elementary school teachers to improve its the quality of learning through K3S (Principal Working Group), while its implementation through KKG (Teacher Working Group) activities. 2) validation lesson study as a model of teacher development to improve its quality of learning through validation on a limited scale programmed by the KKG (Teacher Working Group) at the cluster level in each school, and carried out evaluation, and validation of this lesson study to create active, innovative, creative and fun learning.